2010
DOI: 10.1016/j.jaci.2010.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of allergen-specific desensitization

Abstract: SUMMARY SUMMARYProtective immunity is provided by the interplay between the innate and the adaptive arms of the immune systems. The innate as well as the adaptive immune response is regulated by specialized cells with the challenging task to eliminate pathogens while not damaging the host itself. Usually the immune system copes well with this charge, but is not always successful. Furthermore, proinflammatory lipids, cytokines, and chemokines are produced and released, leading to an allergic inflammation. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 38 publications
3
112
0
Order By: Relevance
“…Immune complexes made of allergen and autologous Abs improved allergy to grass pollen (58). Supporting this in vivo observation, IgG anti-allergen Abs were reported to inhibit allergen-induced basophil activation (20,59). With this system, Cady et al (20) found that FcgRIIA was required for inhibition.…”
Section: Discussionmentioning
confidence: 91%
“…Immune complexes made of allergen and autologous Abs improved allergy to grass pollen (58). Supporting this in vivo observation, IgG anti-allergen Abs were reported to inhibit allergen-induced basophil activation (20,59). With this system, Cady et al (20) found that FcgRIIA was required for inhibition.…”
Section: Discussionmentioning
confidence: 91%
“…The specific IgE level in those animals reached the same level of sensitized mice that were not orally challenged with OVA, but the difference between these two groups regarding the humoral response is in the concentration of specific IgG1. It has been shown that beyond neutralization, IgG (IgG1 in mice and IgG4 in humans) blocks mast cell activation [25] and can even protect IgE-mediated anaphylaxis [26]. Indeed, this is one of the explanations of why the IgE levels do not necessarily decrease during oral immunotherapy despite showing efficiency, both in humans and in murine experimental models [22,23,27].…”
Section: Discussionmentioning
confidence: 99%
“…Allergenic immunotherapy induces shift in the cytokine profile from Th2 subpopulation (IL-4 and IL-5) towards Th1 subpopulation (IFN-gamma) (uermöSi et al, 2010). The most significant role in the development of oral tolerance is played by IL-10 and TGF-β (rollAnd et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a lot of attention has been focused on novel specific immunomodulatory therapies for food allergy, including oral immunotherapy (OIT) and sublingual immunotherapy (SLIT) (BlumcHen et al, 2010;Frew, 2010). Allergen-specific immunotherapy (ASIT) has been reported to modify different aspects of the immune system, inducing shift of allergy-promoting Th2 cells to Th1 cells, epitope-specific T-cell anergy, and allergen-specific regulatory T cells that suppress the responses of effector T cells (ArpS et al, 1998;uermöSi et al, 2010). …”
mentioning
confidence: 99%